The significance of odour concentration measurement uncertainty in the acceptance process of a odour removal installation - Latzke, Małgorzata (Instal, 2025)
A reliable assessment of the effectiveness of odour removal installations is crucial for protecting air quality and reducing odour nuisance. This article analyses the impact of measurement uncertainty on the assessment of the acceptance of installations, taking into account the number of control measurements and the selection of a representative emission value. It was shown that the use of average emission values can lead to an underestimation of the impact, while the use of the upper limit of the 95% confidence interval increases the predicted nuisance range by 80-160 m. It was also pointed out, that there are situations in which the choice of representative value does not affect the assessment. The results emphasize the importance of taking measurement uncertainty into account in the acceptance process of a odour removal installation.
Keywords: measurement uncertainty; odour concentration; odour abatement efficiency; pollutant dispersion modelling; odour nuisance